Deforestasi Hutan Lindung dalam Proyek Pembangunan Pembangkit Listrik Tenaga Panas Bumi Baturraden di Kawasan Lereng Gunung Slamet dan Ancaman Terhadap Human Security Masyarakat di Sekitarnya - Bayu Mahendra; Hermini Susiatiningsih (Journal of International Relations Diponegoro, 2022)
Human Security is the main focus of security in the modern era which focuses on individuals in the international community. The existence of these individuals in the international relations phenomenon among various actors arises due to the development of industry, the technology which recognizes individuals as actors. It occurs because individuals in the era of accelerated development become the harmed actors specifically, in this study, the development of Baturraden geothermal power plant (PLTP Baturraden). This development project leads some threats of the Human Security of surrounding community such as polluting the river water and disrupting the use of water by the community. In this study, the researcher uses the Critical Theory approach proposed by Robert Cox. The case study that is adopted in this study supports the statement that the acceleration of PLTP Baturraden development has caused the river water pollution and various threats to the Human Security of the surrounding community. In conclusion, the result of this study indicates that the application of Good Governance is related to the protection of Human Security.